Sensor and object recognition technologies for self-driving cars. Issue 4 (4th July 2018) - Hirz, Mario; Walzel, Bernhard
ABSTRACT: Autonomous driving functions for motorized road vehicles represent an important area of research today. In this context, sensor and object recognition technologies for self-driving cars have to fulfill enhanced requirements in terms of accuracy, unambiguousness, robustness, space demand and of course costs. The paper introduces different levels of automated driving functions according to the SAE standard and derives requirements on sensor technologies. Subsequently, state of the art technologies for object detection and identification as well as systems under development are introduced, discussed and evaluated in view of their suitability for automotive applications. GRAPHICAL ABSTRACT: